Alteration of m6A RNA Methylation in Heart Failure With Preserved Ejection Fraction - Zhang, Beijian; Xu, Yamei; Cui, Xiaotong; Jiang, Hao; Luo, Wei; Weng, Xinyu; Wang, Yun; Zhao, Yuhong; Sun, Aijun; Ge, Junbo (Frontiers in cardiovascular medicine, 2021)
Background: Heart failure with preserved ejection fraction (HFpEF) is a heterogeneous disease, in which its pathogenesis is very complex and far from defined. Here, we explored the N 6 -methyladenosine (m6A) RNA methylation alteration in patients with HFpEF and mouse model of HFpEF. Methods: In this case–control study, peripheral blood mononuclear cells (PBMCs) were separated from peripheral blood samples obtained from 16 HFpEF patients and 24 healthy controls. The change of m6A regulators was detected by quantitative real-time PCR (RT-PCR). A “two-hit” mouse model of HFpEF was induced by a high-fat diet and drinking water with 0.5 g/L of N ω -nitro-l-arginine methyl ester (L-NAME). MeRIP-seq was used to map transcriptome-wide m6A in control mice and HFpEF mice, and the gene expression was high-throughput detected by RNA-seq. Results: The expression of m6A writers METTL3, METTL4 , and KIAA1429 ; m6A eraser FTO ; and reader YTHDF2 was up-regulated in HFpEF patients, compared with health controls. Furthermore, the expression of FTO was also elevated in HFpEF mice. A total of 661 m6A peaks were significantly changed by MeRIP-seq. Gene Ontology (GO) analysis revealed that protein folding, ubiquitin-dependent ERAD pathway, and positive regulation of RNA polymerase II were the three most significantly altered biological processes in HFpEF. The pathways including proteasome, protein processing in the endoplasmic reticulum, and PI3K-Akt signaling pathway were significantly changed in HFpEF by Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis. Conclusions: The expression pattern of m6A regulators and m6A landscape is changed in HFpEF. This uncovers a new transcription-independent mechanism of translation regulation. Therefore, our data suggest that the modulation of epitranscriptomic processes, such as m6A methylation, might be an interesting target for therapeutic interventions.